Soft skills needed by electrical technology students for 21st century jobs - Olojuolawe, Sunday Rufus (Readers Insight Publisher, 2019)
The study investigated the rise in the rate of unemployment among Electrical Technology graduates from Colleges of Education in Nigeria despite the huge government investment in power and education sectors. The study is a qualitative study which involve a survey of literature and interview protocol. This study is designed to determine the employability skills needed by electrical technology students in Colleges of Education qualitatively with the aimed of suggesting a departure from the general framework available to all disciplines. A review of journal articles and policy documents on Employability skills and Electrical Technology was conducted, leading to the interview data that was conducted among 6 employers of labour and 4 Senior Academic staff in the four Colleges of Education that have Electrical Technology programme in South Western Nigeria. The study revealed that there is a skill mismatch between Colleges of Education in Nigeria and the labour market. Thus, the students lack the skills for 21st-Century jobs. The two results were integrated to come up with a Framework of employability for Electrical Technology students in Colleges of Education in Nigeria. The study observed that the framework developed was still broad and therefore recommends a valid discipline-difference employability skill framework using Rasch Analysis Model to determine the competencies and its hierarchy.